Analisis Pengaruh Tekanan Etis, Orientasi Etis, dan Religiusitas terhadap Praktik Manajemen Laba: Pendekatan PLS-SEM - Wahyu Adi Wibowo (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study was conducted to explore in depth how ethical pressure, ethical orientation, and religiosity influence earnings management practices, while also examining whether religiosity plays a role as a moderating variable in this relationship. Using a quantitative, survey-based approach, this study involved 109 respondents with professional backgrounds and experience in accounting and finance, thus deemed relevant in understanding the phenomenon of earnings management from a practitioner's perspective. The data analysis technique used was Partial Least Square Structural Equation Modeling (PLS-SEM), which is considered appropriate for examining relationships between latent variables with high complexity. The results show that ethical pressure has a positive and significant influence on earnings management practices, meaning that the greater the ethical pressure a person feels, the higher the tendency to engage in such practices. Conversely, ethical orientation shows a negative and significant influence, so that individuals with a strong ethical orientation tend to reject this manipulative practice. Religiosity is also shown to have a significant negative influence, so that the higher a person's level of religiosity, the lower their tendency to engage in earnings management. Furthermore, moderation analysis found that religiosity strengthens the influence of ethical orientation in suppressing earnings management practices, meaning that individuals who are both religious and have a high ethical orientation are more consistent in maintaining their integrity. However, the role of religiosity was not proven to be significant in moderating the relationship between ethical pressure and earnings management practices, indicating that although religiosity can shape ethical attitudes, it is not sufficient to mitigate the impact of strong external pressures. These findings imply the importance of strengthening ethical values ​​and religiosity in accounting education and practice to prevent opportunistic behavior that is detrimental to related parties.